EFFECTS OF Moina sp. FEEDING FREQUENCY ON THE GROWTH PERFORMANCE AND SURVIVAL OF Hemibagrus nemurus LARVAE - Khairul Hadi; Yanata Yudha; Agusnimar Agusnimar; Rosyadi Rosyadi; Andre Sofian (Journal of Fish Nutrition, 2026)
The Asian redtail catfish (Hemibagrus nemurus) is a freshwater species with high economic value and considerable aquaculture potential. However, the development of its culture is still constrained at the hatchery stage, particularly by the low survival rate of larvae during early rearing. This study aimed to evaluate the effect of Moina sp. feeding frequency on the growth performance and survival of H. nemurus larvae. The experiment was conducted for 15 days in June 2025 at the Microalgae and Fish Nutrition Laboratory, Faculty of Agriculture, Universitas Islam Riau, Pekanbaru, Indonesia. A completely randomized design with one factor was applied, consisting of five feeding frequencies and three replicates. The treatments were feeding Moina sp. at frequencies of 1, 2, 3, 4, and 5 times per day. Three-day-old larvae were used, with an initial average body weight of 0.01 ± 0.00 g and an initial average total length of 0.40 ± 0.00 cm. The observed parameters included final weight, final length, absolute weight gain, absolute length gain, specific growth rate, and survival rate. The results showed that feeding frequency had a significant effect on the growth and survival of H. nemurus larvae. The best performance was obtained at a feeding frequency of 5 times per day, resulting in a final weight of 0.09 ± 0.01 g, final length of 1.26 ± 0.01 cm, absolute weight gain of 0.09 ± 0.01 g, absolute length gain of 0.86 ± 0.01 cm, specific growth rate of 18.13 ± 0.38%, and survival rate of 82.00 ± 4.62%. Water quality parameters throughout the experiment remained within acceptable ranges for larval rearing. Therefore, feeding Moina sp. 5 times daily is recommended as the most effective feeding frequency to improve the growth and survival of H. nemurus larvae